2005
DOI: 10.1097/01.sap.0000185656.66239.ad
|View full text |Cite
|
Sign up to set email alerts
|

Closure of the Donor Site of the Free Radial Forearm Flap

Abstract: V-Y local donor site closure is a good technique which prevents an additional donor site scar and discomfort when performing an STSG closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…In the present study, the patients were satisfied with the scarring at the forearm in both groups (FTSG: 5.53; STSG: 6.03 on VAS), and no significant difference was found between the 2 groups ( P = 0.7668). This finding matched the findings of Zuidam, Coert, 24 who found hypertrophic scars in 10.53% of the patients. The heterogeneity of the results in the literature are an indication on how the subjective opinion of the investigator or the patient influences the results of the outcome.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the patients were satisfied with the scarring at the forearm in both groups (FTSG: 5.53; STSG: 6.03 on VAS), and no significant difference was found between the 2 groups ( P = 0.7668). This finding matched the findings of Zuidam, Coert, 24 who found hypertrophic scars in 10.53% of the patients. The heterogeneity of the results in the literature are an indication on how the subjective opinion of the investigator or the patient influences the results of the outcome.…”
Section: Discussionsupporting
confidence: 91%
“…Murray et al (2011) similarly concluded dermal substitutes provide advantages, however, not all patients (10%) could not return to the operating room for the second stage of skin grafting, and had resultant hypertrophic scarring. Also, graft uptake was still only 84%, which is not much of an improvement from other studies of traditional skin grafting methods (D'Arpa et al, 2018;Davis et al, 2011;Zuidam et al, 2005). Other synthetic dermal substitutes (Matriderm and amniotic membranes), used with STSG, have also shown success related to aesthetics and function, but there are not enough comparative studies to draw any conclusions at this time (Cristofari et al, 2020;Patel, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…Eight studies were included in the final systematic review (D'Arpa et al, 2018; Davis et al, 2011; Ho et al, 2006; Krane et al, 2020; Molteni et al, 2022; Sidebottom et al, 2000; Thiele et al, 2008; Zuidam et al, 2005). This included a total of 366 skin grafts, 197 STSG and 169 FTSG.…”
Section: Resultsmentioning
confidence: 99%
“…Fibula donor sites were closed with split-thickness skin grafts and negative pressure dressing (VAC W ) dressings. A full-thickness skin graft taken from the upper forearm described by Zuidam et al 4 was used for closure of RFF donor site in all cases.…”
Section: Types Of the Flap And Operative Particularsmentioning
confidence: 99%